How to manage plant biomass originated from phytotechnologies? Gathering perceptions from end-users. Issue 10 (3rd October 2017) - Bert, V.; Neub, S.; Zdanevitch, I.; Friesl-Hanl, W.; Collet, S.; Gaucher, R.; Puschenreiter, M.; Müller, I.; Kumpiene, J.
ABSTRACT: A questionnaire survey was carried out in four European countries to gather end-user's perceptions of using plants from phytotechnologies in combustion and anaerobic digestion (AD). Nine actors of the wood energy sector from France, Germany, and Sweden, and eleven AD platform operators from France, Germany, and Austria were interviewed. Questions related to installation, input materials, performed analyses, phytostabilization, and phytoextraction were asked. Although the majority of respondents did not know phytotechnologies, results suggested that plant biomass from phytomanaged areas could be used in AD and combustion, under certain conditions. As a potential benefit, phytomanaged plants would not compete with plants grown on agricultural lands, contaminated lands being not suitable for agriculture production. Main limitations would be related to additional controls in process' inputs and end-products and installations that might generate additional costs. In most cases, the price of phytotechnologies biomass was mentioned as a driver to potentially use plants from metal-contaminated soils. Plants used in phytostabilization or phytoexclusion were thought to be less risky and, consequently, benefited from a better theoretical acceptance than those issued from phytoextraction. Results were discussed according to national regulations. One issue was related to the regulatory gap concerning the status of the plant biomass produced on contaminated land.